PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI VARIABEL MEDIASI (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI pada Tahun 2013-2015) - Mohamad Arif Khakim, 13.05.52.0127; Suwarti, Titiek (Students' Journal of Accounting and Banking, 2017)
This study aims to examined and analyzed the effect of profitability and leverage on firm value with corporate social responsibility as a mediation variable on manufacturing companies listed in the Indonesia Stock Exchange. The population of this research is manufacturing companies listed in the Indonesia Stock Exchange (IDX) wich reports the annual report and financial statements wich complete during the year 2013-2015 in a row. The samples are included in the criteria of this study were 165 companies using purposive sampling method. This research data analysis methods using the multiple linear regression analysis. The result of the research shows that the first model profitability variables do not have an effect on corporate social responsibility (CSR) and leverage variable have effect to corporate social responsibility (CSR). In the second model profitability, leverage, and corporate social responsibility (CSR) have effect to firm value. As a mediation variable corporate social responsibility (CSR) is not able to mediate the relationship of profitability and leverage to the firm value. Keywords: Firm Value, Corporate Social Responsibility, Profitability, Leverage